Spirobifluorene-based non-fullerene acceptors for the environmentally benign process. (September 2020) - Sung, Min jae; Park, Byoungwook; Choi, Ji Young; Kim, Jehan; Sun, Cheng; Kang, Hongkyu; Kwon, Sooncheol; Jang, Soo-Young; Kim, Yun-Hi; Lee, Kwanghee; Kwon, Soon-Ki
Abstract: Spirobifluorene based non-fullerene acceptors (NFAs) having meta -ethylhexyl oxy (m-OEh) substituents (PBDB-T: spiro-bridged NFAs) were synthesized. The orthogonal molecular structure of the m-OEh-substituted spirobifluorene with different end groups provided high solubility and kept the stable morphology between donor-acceptor. Organic Photovoltaic (OPV) device performance was not significantly affected by switching the processing solvent from a chlorinated solvent to an environmentally benign solvent, because suitable morphology and crystallinity were retained. The ITO/ZnO/PBDB-T:spiro-bridged NFA/MoOx /Ag OPV devices prepared using a chlorobenzene as the processing solvent displayed maximum efficiency in the range of 6.44–5.78%, while the devices made using xylene as the processing solvent had a lower maximum efficiency ranging from 6.14–4.66%. The OPV performance of the devices made using chlorobenzene decreased in the order of sp-mOEh-ITIC > sp-mOEh-ITIC-M > sp-mOEh-ITIC-F > sp-mOEh-ITIC-Cl because an electron donating end group increased open-circuit voltage ( V oc), while the electron withdrawing end group increased the short-circuit current density ( J sc). Although the OPV performance of the four spiro-bridged derivatives by xylene was showed to be similar order of that by chlorobenzene solvent processing, the efficiency drop from chlorobenzene solvent to xylene solvent showed following order sp-mOEh-ITIC < sp-mOEh-ITIC-M < sp-mOEh-ITIC-F < sp-mOEh-ITIC-Cl, which depended on the polarity effect of end groups. Graphical abstract: Image 1 Highlights: Spirobifluorene-based Non-fullerene Acceptors. End-group effect of spirobifluorene-based Non-fullerene Acceptors. Solar cell devices in chlorobenzene generated PCE of 6.44–5.78%. Environmentally benign process showed PCE of 6.14–4.66%.